Genre-based Pedagogy: A case of an Iranian ESP Business Management course - Asl, Hadis Toufani (Widya Mandala Catholic University Surabaya, 2015)
Genre-based instruction has been latterly a very common method used in language courses. In spite of the various research conducted on academic genres, there are still very few studies which examine the learners’ perceptions of genre-based pedagogy, particularly in courses like English for Specific Purposes (ESP). Therefore, the present study aimed at considering the Sophomore Business Management learners’ perspective on genre instruction in their ESP course, at the University of Tehran. The focuses of the present study were the focal genres of textbook and teaching method in terms of the content feature. The data was collected by means of both quantitative and qualitative instruments which were subject to both statistical analysis and constant comparative method of qualitative analysis. Results of the study revealed that the practice of genres were relevant to some of the learners’ subsequent academic and non-academic performance. Furthermore, the results regarding the questionnaire section indicated that a number of learners could apply the genre features and they were conscious of them. By and large, it was concluded that the explicit instruction together with the provision of more English-mediated content courses, for practices outside of the classroom, can have a higher impact on ESP programs. Keywords: ESP, genre-based pedagogy, content, textbook, teaching method, activities, learners’ perception